Influence of the source of pollen on the oil content of maize grains - Batista, Luiz A. Rocha; Tosello, Geraldo A. (Pesquisa Agropecuaria Brasileira, 2014)
The present study evaluated the effects of source of pollen on the oll content of maize grains (Zea mays L.). Seed was used from two ears from the same plant, one that was self-fertilized and the other one open-pollinated. The work was conducted with germplasm ESALQ VF 1, an orange-coloured, hard grain type. The results of the analysis of oil content showed that there was an inbreeding depression of 4%, indicating the effective participation of source of pollen in the germplasm studied. In improvement programs to increase the oil content in maize grains, in this germplasm, progenies can be selected either through self-fertilized seeds or by open-pollination since the linear correlation between the two types of seeds was high and positive (r = 0.67**). The use of open-pollinated seed would mean lower operating costs in the program. Since this characteristic is being determined by the genotype of its own seed, it represents available genetic variation between seed of the same ear.